Structures Of Surfaces With Non-Zero Constant Curvature - Hossain, Mohd Altab (GANIT: Journal of Bangladesh Mathematical Society, 2013)
In this paper, surfaces of positive constant curvature and those of negative curvature are studied. In certain cases, a very few important structures of this class of surfaces have been obtained. DOI: http://dx.doi.org/10.3329/ganit.v32i0.13644 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 32 (2012) 37-41